Analysis of the Nature of Science in the â€œMerdekaâ€ Curriculum and Elementary Science Books and Their Comparison Between Countries - Ika Rosmiati; Nurul Saadah Agustina; Yusup Maulana; Ari Widodo (Jurnal Penelitian Pendidikan IPA, 2022)
The nature of science is essential to be conveyed in the curriculum and student books because it becomes a reference in the learning process to adequately achieve learning objectives. This study aims to describe aspects of the nature of science in the "merdeka" curriculum and its comparison between countries and an analysis of the nature of science in elementary science books. The quantitative descriptive method is carried out by studying literature and analyzing documents on aspects of the nature of science in the "merdeka" curriculum documents and elementary science books. Curricula documents from other countries are analyzed to find out the comparison. Based on the analysis and comparison results, it is shown that the nature of science in the elementary school curriculum and its embodiment in student books is not explained explicitly, both in the curriculum and in student books. The percentage of science essence values â€‹â€‹in the student curriculum is > 80.00%, namely product, subjective, and creative aspects, and in student books, only product aspects have a percentage value of > 80.00%. It is known that the percentage of the emergence of the nature of science is different in each country.